2023
DOI: 10.1039/d3qo00457k
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective synthesis of five- and six-membered carbocycles via Matteson homologation/ring closing metathesis

Abstract: The Matteson homologation is found to be a versatile tool for the stereoselective synthesis of polyunsaturated alkyl boronic esters, which can be used for the construction of five- and six-membered carbocycles via ring-closing metathesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…The observation that allylboronic esters can, in principle, undergo allyl isomerization under certain conditions was reported by Brown et al, although these investigators observed this reaction by heating boronic esters in toluene for more than 24 h . Although the linear product 6 was not initially anticipated, we were still able to use it for further Matteson homologations in combination with ring-closing metathesis reactions …”
supporting
confidence: 56%
See 2 more Smart Citations
“…The observation that allylboronic esters can, in principle, undergo allyl isomerization under certain conditions was reported by Brown et al, although these investigators observed this reaction by heating boronic esters in toluene for more than 24 h . Although the linear product 6 was not initially anticipated, we were still able to use it for further Matteson homologations in combination with ring-closing metathesis reactions …”
supporting
confidence: 56%
“…The observation that allylboronic esters can, in principle, undergo allyl isomerization under certain conditions was reported by Brown et al, although these investigators observed this reaction by heating boronic esters in toluene for more than 24 h. 18 Although the linear product 6 was not initially anticipated, we were still able to use it for further Matteson homologations in combination with ring-closing metathesis reactions. 19 To determine when the allyl isomerization occurred, we used nuclear magnetic resonance (NMR) to analyze the crude α-chloroboronic ester 5 formed in the reaction, which clearly indicated that the terminal double bond of compound 3 had disappeared and a (E)-configured substituted double bond had formed. The same intermediate 5 and product 6 were obtained from (E)-crotylboronic ester C (Scheme 2).…”
mentioning
confidence: 99%
See 1 more Smart Citation